Modelling batting expertise from the perspective of high performance coaches - Connor, J. D.; Renshaw, I.; Farrow, D.; Abernethy, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Cricket coaching literature on developing batting expertise has largely focused on the individual, and typically, technical features of batting. Research in cricket batting has addressed developmental factors of expertise (Weissensteiner, et al., 2009) or the perceptual advantage of expert batters (Muller & Abernethy, 2006). Little attention has been paid to the importance of the individual-environment relationship in expert behaviour. In order to address this missing ingredient, one on one, in-depth, semi- structured interviews were undertaken by the primary researcher with eight high performance coaches (e.g., international or state) who were purposively sampled from Cricket Australia or State Cricket associations. Six of these coaches had played international cricket as batsmen, one played state level and one a first grade player. Interviews were transcribed verbatim and coded separately by the first and second author after each interview. The third author then reviewed all codes and provided feedback. Strategies used to enhance validity included; sampling coaches of different high performance levels and retrospective member checking with coaches. Key themes that emerged include expert`s superior knowledge of, and attunement to internal (e.g., emotions) and external (e.g. pitch type, field settings) information. This informs their intentions, perceptions and actions to achieve the task goal at any game moment. A skilful batter has time to execute their action and is in `rhythm` with the bowler through attunement to specifying information sources. Experts also adapt to and manipulate the performance environment. Self-evaluative processes, through between-ball routines provide opportunity to reflect, re-evaluate and plan for the next delivery. Examples include; changing stance, forcing field changes or manipulating bowler`s emotions. These results highlight the importance of capturing the experiential knowledge of high performance coaches that cannot be obtained through traditional laboratory based studies. For cricket batting coaches, this work emphasizes the importance of designing learning environments that enable players to better understand their own performance in the context of emergent dynamic game-based constraints.